Performative "Wokeness": Exploring Blacks' perceptions of White Allies who confront anti-Black racism - Crittle, Chelsea. (2017)
Abstract: How does the racial identity of someone who confronts racial bias effect how the message is perceived? Earlier work on persuasion and confrontation has examined aspects of the messenger, message, and perceiver in the effectiveness of confronting racial bias. Given that past research has focused on non-stigmatized individuals' (e.g. Whites, men) perceptions of stigmatized individuals (e.g. Blacks, women), the current experiments focused on Blacks' perceptions of White messengers. In Experiment 1, Black and White participants evaluated a Black or White messenger who wrote an article making an extreme, mild, or no claim of racial bias. We hypothesized that Black messengers giving extreme messages will receive more backlash than White messengers among White perceivers. However, this pattern should reverse for Black perceivers, with White messengers receiving greater backlash than Blacks. Findings did not support the hypotheses. Experiment 2 was designed to address limitations and unresolved issues in Experiment 1. Findings from this study provided evidence for a race-specific evaluative backlash against White messengers who make mild claims. Furthermore, perceptions of the messengers' group-based guilt fully mediated the three-way interaction between messenger race, participants race, message extremity and backlash. Overall, these findings identify some conditions under which White individuals can or cannot effectively discuss racial bias amongst stigmatized individuals; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Psychology.; Advisor: Keith Maddox.; Committee: Alex Czopp, and Samuel Sommers.; Keyword: Social psychology.